해양경찰 정보활동의 법적 근거와 범위에 관한 고찰 - 최정호 (한국해양경찰학회보, 6(2), 2016)
해상정보활동은 “해상에서 국가안보나 국가이익, 국가정책결정을 위해 사용자에게 제공할 목적으로 수집․분석한 결과물 또는 그러한 활동”이라고 정의할 수 있다. 2014. 11. 19. 해양경찰청이 해양경비안전본부로 재편된 이후, 정보기능의 조직과 인원이 상당히 축소된 상태이지만, 해상정보활동을 수행하기 위하여 해양경찰 정보활동 조직을 현실에 맞게 조정하여야 한다. 그러기 위해서는 해양경찰 정보인력의 축소에 맞게 과거에서부터 해오던 업무로부터의 부담을 줄여주어야 하고, 해양수산 분야의 정책정보 기능을 수행할 수 있도록 집중하여야 하며, 해양경찰 정보기능에 맞게 조직의 명칭도 개선하여야 한다. 해상정보활동이 내실 있게 수행되기 위해서는 법률적인 보완도 필요하다. 해양경찰 정보관들이 자신감을 가지고 직무를 수행할 수 있도록 해상정보활동에 대한 법적인 근거를 숙지할 수 있는 기회를 부여하고, 정보기능을 수행하기 위해서는 반드시 정보전문화 교육을 이수할 수 있도록 내부규정화하여야 하며, 해양경찰의 정보활동과 관련된 내용이 해양경찰 조직 또는 집행과 관련된 법률에 규정되도록 노력하여야 한다. 해상정보활동이 국가 정책결정에 있어서 중요한 역할을 담당할 수 있도록 하기 위해서는 해양경찰 정보활동만의 특화된 분야를 개발하여야 한다. 우선은 선박을 중심으로 전문화된 해상정보활동이 이루어져야 하고, 북한과 대치되는 특별한 상황에서 해상보안업무는 해양경찰이 전담하여야 하며, 바다와 관련된 각종 정보를 다루는 관련 기관과 해상정보를 연계하고 공유함으로써 국민에게 해양과 관련된 최고의 서비스를 제공하는 해양정보 생태계를 구축하여야 한다. Maritime intelligence is defined as “information collected and analyzed on the sea to provide the result to the users for national security, national interest, and national policy-making, or the relevant activities.” Since the Korea Coast Guard was affiliated to the Ministry of Public Safety and Security on November 19, 2014, the organization and the number of staff for maritime intelligence have been considerably reduced. However, the maritime intelligence organization of the former Korea Coast Guard should be adjusted to the reality to perform maritime intelligence. For this, according to the downsized Korea Coast Guard intelligence organization, the workload from past tasks should be reduced, the intelligence activities should be concentrated on the information relevant to maritime affairs and fisheries policies, and the name of the organization should be revised in harmony with the maritime intelligence functions of Korea Coast Guard. Substantial maritime intelligence activities require legal supplementation. The intelligence officers of Korea Coast Guard should be given opportunities to fully understand the legal basis of maritime intelligence activities so that they have confidence in their works. An internal regulation should be established for intelligence officers to definitely undergo an intelligence expertise education for performing intelligence functions. Efforts should be made so that the information about the maritime intelligence activities by Korea Coast Guard may be regulated in the law relevant to the organization or enforcement of Korea Coast Guard. In order to make maritime intelligence play an important role in national policy-making, activities specialized for the maritime intelligence of Korea Coast Guard should be developed. First, the specialized maritime intelligence should be carried out with respect to ships. The maritime security works should be carried out exclusively by Korea Coast Guard in particular situations where there is a confrontation with North Korea. A maritime intelligence system should be established to provide the best maritime service to the citizens by sharing various types of maritime information with relevant institutions. KCI Citation Count: 3